Productivity and nutrient use of sunflower (Helianthus annuus L.) in sequential cropping system in Vertisols: PRODUCTIVITY AND NUTRIENT USE OF SUNFLOWER IN SEQUENTIAL CROPPING SYSTEM IN VERTISOLS - G SURESH; S N SUDHAKARA BABU; A AZIZ QURESHI (Journal of Oilseeds Research, 2015)
Field experiments were conducted on fixed plot for three consecutive years during 2009-12 onmediumVertisols at Hyderabad. The experimental site was clay soil with a soil pH and organic carbon of 7.7 and 0.51 per cent, respectively. The productivity and sustainability ofrabi sunflower was assessed under three cropping sequences in rainy(kharif) and winter (rabi)seasons viz., fallow-sunflower; sunflower-sunflower and soybean-sunflower and four nutrient management practices. The kharif crops were grown as rainfed and rabi sunflower was grown with one irrigation at sowing. The highest seed yield (1412 kg/ha) of sunflower was recorded in soybean-sunflower system followed by fallow-sunflower (1185 kg//ha) system. Continuous cropping ofsunflower resulted in lowest yield (983 kg/ha). N and P uptake of rabi sunflower succeeding either soybean or fallow was higher compared to continuous cropping. Significantly higher and comparable seed yield, stalk yield were obtained with the application of recommended dose of major nutrients in conjunction with farm yard manure (FYM).